The Ottoman Empire: From Conquest and Integration of the Peripheries to Attempts of Modernization - Allamuratov, Anvar (Pubmedia Social Sciences and Humanities, 2025)
The Ottoman Empire, spanning from 1299 to 1923, developed a unique imperial system by integrating elements from ancient Eastern empires, the Byzantine tradition, and the Islamic Caliphate. This empire ruled over diverse ethnic and religious groups, demonstrating remarkable adaptability in governance. The Ottoman rulers aimed to extend their influence across the Mediterranean, striving to create a powerful empire comparable to Rome. Their expansionist policies were driven by military innovation and economic structures that prioritized imperial wealth and the sustainability of the ruling elite. However, internal challenges, economic transformations, and external pressures led to the empire's gradual decline. This article examines the mechanisms of conquest, integration of peripheral regions, and modernization attempts, highlighting the empire’s resilience and ultimate dissolution.